ANALISA SWOT KEBERHASILAN USAHA PADA PRODUK PEWANGI LAUNDRY “MJL” (STUDI PADA TOKO HAYYU BERKAH DI CIKARANG SELATAN) - Biaggi Armanda Susilo; RR. Wening Ken Widodasih; Kurbandi Satpatmantya BR (Jurnal Ilmiah Global Education, 2023)
Laundry perfume is a liquid with a chemical base made from a variety of mixed ingredients that can be used to scent clothes. With a wide determination of fragrance fragrances to perfume the clothes of the clothes. The laundry at the laundry is dominated by this fragrance. Even when opened from the packaging, the scent of the clothes is completely absorbed and when worn it will feel refreshing. This laundry perfume can be used to scent washed clothes when they are washed, when they are ironed by spraying, and when they are packed. Please note that the perfume used in all three processes must be the same. This study aims to analyse the Swot Analysis of Business Success in Laundry Fragrance Products "MJL" (Study at Hayyu Berkah Store in South Cikarang). Collect data through interviews, observation, and documentation. Primary and secondary data will be used by researchers in this study. Direct interviews with informants, especially the owner of Hayyu Berkah Shop in South Cikarang were used to collect primary data. This interview includes a list of questions. Since primary data is only collected after the research project is developed, there is no risk of outdatedness. Secondary data is information collected by researchers from government agencies, books or journals, and library data. Based on the SWOT analysis that has been conducted, it can be concluded that the "MJL" laundry fragrance product business has strengths including quality products, competitive prices, and a wide market reach. However, this business also has several weaknesses such as lack of promotion and marketing, and dependence on several raw material suppliers.